1271. Efficacy and Safety of Cefiderocol and Best Available Therapy in Patients with Serious Infections Caused by Carbapenem-Resistant Gram-Negative Infections: Results of the Pathogen-Focused Phase 3 CREDIBLE-CR Study. (31st December 2020) - Bassetti, Matteo; Echols, Roger; Matsunaga, Yuko; Portsmouth, Simon; Ariyasu, Mari; Toyoizumi, Kiichiro; Doi, Yohei; Doi, Yohei; Den Nagata, Tsutae
Abstract: Background: The CREDIBLE-CR study assessed the efficacy and safety of cefiderocol (CFDC), a novel siderophore cephalosporin, in the treatment of serious infections due to carbapenem-resistant (CR) Gram-negative (GN) bacteria. Methods: CREDIBLE-CR was an open-label, prospective, randomized 2:1, Phase 3 study (NCT02714595) in patients with nosocomial pneumonia (NP), bloodstream infections/sepsis (BSI/Sepsis), or complicated urinary tract infections (cUTI) with evidence of CR GN pathogens. Adults received intravenous CFDC 2 g, q8h, 3-h infusion or best available therapy (BAT; up to 3 drugs) for 7–14 days (extendable to 21 days). The primary endpoint at test of cure in the CR microbiological intent-to-treat (CR-MITT) population was clinical cure (NP, BSI/Sepsis) or microbiological eradication (cUTI). Secondary endpoints were clinical and microbiological outcomes, all-cause mortality (ACM) and safety. Only descriptive statistics were pre-specified. Results: A total of 101 patients received CFDC and 49 received BAT (CR-MITT: CFDC n=80, BAT n=38): 50% had pneumonia, 31.4% BSI/Sepsis, and 18.6% cUTI (Table 1). Most frequent CR pathogens were Acinetobacter baumannii (45.8%), Klebsiella pneumoniae (37.3%), and Pseudomonas aeruginosa (23.7%). CFDC monotherapy was given to 83% of patients, while BAT monotherapy to 29% of patients. Primary outcome in the CFDC and BAT arms was achieved in 50.0% and 52.6% in NP, 43.5% and 42.9% in BSI/Sepsis, and 52.9% and 20.0% in cUTI patients (Figure). CFDC was highly efficacious vs CREs and NDM-producing pathogens. Day 28 ACM was 24.8% (25/101) with CFDC and 18.4% (9/49) with BAT. Rescue therapy was given more frequently in the BAT than CFDC arm. Mortality results by pathogen showed an imbalance in Acinetobacter spp. infections (Table 2) with a higher rate in the CFDC arm than BAT arm. ICU and shock at randomization were more frequent in the CFDC arm than in the BAT arm in Acinetobacter spp. infections (Table 2). No safety concerns related to CFDC emerged. Table 1. Baseline demographics and characteristics (CR-MITT population) Figure. CREDIBLE-CR study primary efficacy endpoints and secondary outcomes at test-of-cure visit in CR-MITT population. Table 2. All-cause mortality by baseline pathogen inpatients with or without Acinetobacter spp. infection (safety population) Conclusion: Efficacy of CFDC was demonstrated in this descriptive pathogen-focused study, including CREs, metallo-NDM producers and CR non-fermenters. Baseline imbalances of ICU and shock in the subset of infections with Acinetobacter spp. may have contributed to the mortality difference between CFDC and BAT arms. Disclosures: Matteo Bassetti, MD, Shionogi Inc. (Advisor or Review Panel member) Roger Echols, MD, Shionogi Inc. (Consultant) Yuko Matsunaga, MD, Shionogi Inc. (Employee) Simon Portsmouth, MD, Shionogi Inc. (Employee) Mari Ariyasu, BPharm, Shionogi & Co., Ltd. (Employee) Kiichiro Toyoizumi, PhD, Shionogi & Co., Ltd. (Employee) Tsutae Den Nagata, MD, Shionogi & Co., Ltd. (Employee)